Transformative Islamic Education for Society 5.0: Integrating Artificial Intelligence, Character Education, and Sustainable Development in Bangladesh - Rajarshi Dasgupta (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
The emergence of Society 5.0 has created new challenges and opportunities for educational institutions, particularly in integrating technological innovation with ethical and sustainable human development. In the context of Islamic education, the adoption of Artificial Intelligence (AI) offers significant potential to enhance learning effectiveness while simultaneously raising concerns regarding moral values, character formation, and social responsibility. This study aims to explore the role of transformative Islamic education in integrating Artificial Intelligence, character education, and sustainable development within the context of Bangladesh. Using a qualitative research approach, data were collected through in-depth interviews, observations, and document analysis involving educators, students, and educational stakeholders from Islamic higher education institutions. The findings reveal that AI can support personalized learning, improve access to educational resources, and strengthen digital literacy among students. However, the successful implementation of AI in Islamic education requires a balanced approach that prioritizes ethical principles, character development, and sustainability values. The study demonstrates that Islamic education provides a comprehensive framework for integrating technological advancement with values such as honesty, responsibility, justice, empathy, and environmental stewardship. Furthermore, character education serves as a critical mechanism for ensuring that technological competencies are accompanied by moral awareness and social accountability. The integration of Sustainable Development Goals (SDGs) within Islamic educational practices also contributes to preparing students to address contemporary social, economic, and environmental challenges. This study proposes a transformative model of Islamic education for Society 5.0 that combines AI-driven learning, character-based education, and sustainability-oriented development. The findings contribute to the growing discourse on educational transformation and offer practical recommendations for policymakers, educational institutions, and stakeholders seeking to modernize Islamic education while preserving its ethical and spiritual foundations.